Διερεύνηση του θέματος της χαμένης οικειότητας μέσα από το σχέδιο και τη φωτογραφία - Χρίστου, Παναγιώτης (My University, 2025)
This study explores the theme of lost intimacy through the mediums of drawing and photography. It focuses on how various artistic materials and techniques influence the viewer’s emotional response and contribute to the development of a new narrative that reflects changes in personal and collective memory. The first section centers on the analysis of drawing materials and visual elements—such as lines, texture, and contrasts—examining how these provoke emotional and sensory reactions. Through the study of works by distinguished artists, the emotional impact of visual languages is analyzed, as well as how they enhance the narrative and emotional weight of a piece. The second section discusses the themes and techniques used in the creation of the artistic works, referencing an experimental animated short film titled Please, Remember (2024), which served as the starting point for the research. The works explore the theme of lost intimacy in relation to familiar people, places, and objects, with an emphasis on how the combined use of visual media can convey the emotional burden of this subject. The study aims to offer a critical perspective on memory, loss, and identity through art, highlighting the transformative role of visual media in reshaping familiar perceptions and experiences.
Keywords: Drawing; Photography; Collective memory; Visual media; Οικειότητα; Κάρβουνο; Σχέδιο; Φωτογραφία; Μνήμη; Χαρακτική